Structure Characterization and in Vitro Fermentation of Polysaccharides from Euodiae Fructus - ZHANG Zihao, ZHANG Xiaoxin, FAN Chunjuan, WANG Junqiao, NIE Shaoping (Shipin Kexue)
In this study, a purified polysaccharide from Euodiae Fructus (EFP-40) was obtained by sequential water extraction, decolorization, and gradient ethanol precipitation. Chemical methods such as colorimetry and methylation, as well as instrumental techniques such as high performance gel permeation chromatography (HPGPC), gas chromatography-mass spectrometry (GC-MS), and high performance anion exchange chromatography coupled with an amperometric detector (HPAEC-PAD) were used to characterize its physicochemical properties and structural characteristics. An in vitro fecal fermentation model was established to determine the effect of EFP-40 on the gut microbiota and short-chain fatty acids (SCFAs) production. Results indicated that the molecular mass of EFP-40 was 9.7 × 104 Da, mainly consisting of rhamnose (4.36%), glucose (10.24%), arabinose (22.24%), galactose (24.79%) and galacturonic acid (33.36%). The degrees of methyl esterification (DM) and acetylation (DA) were 17.06% and 8.12%, respectively, and the polysaccharide was possibly a complex pectin containing structural domains such as RG-I (rhamnogalacturonan I) and homogalacturonan (HG). In addition, EFP-40 promoted the production of SCFAs, and regulated the gut microbiota by increasing the relative abundance of beneficial bacteria such as Bacteroidetes and Phascolarctobacterium, reducing the relative abundance of harmful bacteria such as Fusobacteriota and Proteobacteria, as well as the ratio of Firmicutes to Bacteroidetes. In conclusion, EFP-40 is a highly branched complex pectic polysaccharide, which can significantly regulate the gut microbiota, indicating its prebiotic potential.